Prosthetic fitting, use, and satisfaction following lower-limb amputation: A prospective study - Webster, Joseph B. (J Rehabil Res Dev, 2012)
Providing a satisfactory, functional prosthesis following lower-limb amputation is a primary goal of rehabilitation. The objectives of this study were to describe the rate of successful prosthetic fitting over a 12 mo period; describe prosthetic use after amputation; and determine factors associated with greater prosthetic fitting, function, and satisfaction. The study design was a multicenter prospective cohort study of individuals undergoing their first major lower-limb amputation because of vascular disease and/or diabetes. At 4 mo, unsuccessful prosthetic fitting was significantly associated with depression, prior arterial reconstruction, diabetes, and pain in the residual limb. At 12 mo, 92% of all subjects were fit with a prosthetic limb and individuals with transfemoral amputation were significantly less likely to have a prosthesis fit. Age older than 55 yr, diagnosis of a major depressive episode, and history of renal dialysis were associated with fewer hours of prosthetic walking. Subjects who were older, had experienced a major depressive episode, and/or were diagnosed with chronic obstructive pulmonary disease had greater functional restriction. Thus, while most individuals achieve successful prosthetic fitting by 1 yr following a first major nontraumatic lower-limb amputation, a number of medical variables and psychosocial factors are associated with prosthetic fitting, utilization, and function.